Bookplates - Lindsay, Lionel, Sir, 1874-1961. (1921)
A collection of bookplates done by Lionel Lindsay for selected Australian artists, writers, politicians, photographers, book collectors and publishers. Includes bookplates for Robert Menzies, Harry Chaplin, Walter Jeffrey, Keith Murdoch, Peter Lindsay, James Robert McGregor, Clive Fitts, Sydney Ire Smith and Keith Wingrove.
Signed l.l.
Individual bookplates have been catalogued and digitised.
Title taken from cover of album.
The art of Sir Lionel Lindsay / Joanna Mendelssohn
Also available online
Keywords: Bookplates, Australian -- Pictorial works